Oral manifestation of thrombocytopenia in immunosuppressed patient - Report of case - Lima, Antonio Adilson Soares de; Melo, Norma Suely Falcao de Oliveira; Gil, Francisca Berenice Dias (Journal of Oral Diagnosis, 2016)
Thrombocytopenia (or thrombopenia) is a relative decrease of platelets in blood.This condition is associated with increased mortality rates in critically ill patients. It is especially present in cases of sepsis, but can also be caused by medications or associated with the use of foreign materials. Many physiological mechanisms (immune-mediated, consumption or destruction) are involved in the decrease of platelet count. This manuscript describes a case of severe thrombocytopenia with oral manifestation in immunosuppressed patient. A 39-year-old male was admitted to the Hospital Oswaldo Cruz complaining of bleeding in the lower lip. Epistaxis, crusts on the lips and red lesions in the hard palate were observed.